Running Microsoft Powerpoint 97 - Sagman, Stephen W. (Microsoft P. RedmondUS, 1997)
Teaches the basics of the Powerpoint environmenmt. Provides 9 essential steps for creating presentations. Advises on modifying presentations; adding annotations and graphics; and, creating and using 35-mm slides. Assumes a working knowledge of Windows 95 and Windows NT.